THE EFFECTIVENESS OF MODEL-ELICITING ACTIVITIES (MEAS) APPROACH TOWARD STUDENTS MATHEMATICS LEARNING OUTCOMES - Anisa Ulfa Muharomah; Harina Fitriyani (Universitas Ahmad Dahlan, 2018)
Monotonous and teacher-centered learning makes students passive and lacks the courage to express opinions in teaching and learning activities. Therefore, an appropriate model is needed to encourage student activeness, which is with model-eliciting activities. This study aims to determine whether there is a difference between learning by using model-eliciting activities and traditional class models. This model is more effective between the two models of the learning model on student learning outcomes. The population in this study consisted of class VII Muhammadiyah Junior High School Banguntapan (SMP Muhammadiyah Banguntapan), which consists of five classes. A sample of 2 classes with the number of 60 students was taken by purposive technique and obtained class VII C as the experimental class and class VII D as control class. The research instrument is a problem-solving test with data analysis using a two-part hypothesis test and a one-party hypothesis test. The results of a hypothesis test of the experimental class with a significant level of 5% and df=58 showed that: (1) There was a difference between students' problem-solving abilities using learning model eliciting activities with problem-solving skills of students learning using traditional class models and (2) eliciting activities model more effectively than traditional class models of problem-solving abilities.